Librarians as high-impact research data experts / Md Razib Karno, Mohd Subha Salleh and Rafidah Abd Rahim - Karno, Md Razib; Salleh, Mohd Subha; Abd Rahim, Rafidah (Faculty of Information Management, 2023)
High-impact research data assessment can be performed by librarians because they have more knowledge and understanding of managing scholarly publications and research data compared to staff in other departments and are able to identify the research cycle. The role of librarians in the field of library management is constantly evolving. With the increasing importance of big data, organizations are facing a major challenge in storing, managing, analyzing, and using large data sets. In addition, the establishment of data science programs at institutions has meant that librarians must adapt and integrate growing expertise in management, accessibility, and technology to support data scientists. With their expertise and knowledge in data management, analysis, and preservation, librarians are increasingly seen as potential candidates for the role of chief data officer. The result of this report is an analysis of the need for librarians and the expertise that is a priority in the organization, as measured by variables that are the main key, namely, the 7 main megatrends that have a great impact on the analysis, i.e., the 7 key trends that have the greatest impact on this analysis. The results of this study show that the ability of library managers to manage scholarly research data has been demonstrated through their involvement as intermediary librarians or knowledge management officers (KMOs) in faculty, research groups, research consortia, rating audits, institutional hierarchy secretariats, and other needs at the university, organizational, and international levels. This role has also been shown to contribute to the development of a better scientific community, whether as infrastructure developers, setting new policies, working on data governance, effective data integration, training and promotion, and more.